2011
DOI: 10.4103/0301-4738.83612
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral versus unilateral thyroid eye disease

Abstract: Aims:The aim of this study was to compare demographics, clinical manifestations, associated systemic and ocular factors, severity and activity of patients with unilateral thyroid eye disease (U-TED) versus bilateral thyroid eye disease (B-TED).Materials and Methods:In a cross-sectional study, all patients with Graves’ hyperthyroidism and primary hypothyroidism seen in an endocrinology clinic were included from September 2003 to July 2006. Demographics, complete eye examination, severity score (NOSPECS, total e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 11 publications
1
37
2
Order By: Relevance
“…We recently showed that there is no significant difference between unilateral vs bilateral TED regarding the demographics, type of thyroid disease, associated findings, and severity and activity of TED. 15 Our data indicated that patients with U-TED belonged to the same population as those with bilateral eye disease. 15 Similar to Eckstein et al, 3 we found no significant difference with regard to the age, gender, and smoking habit between Hr-TED vs Ho-TED (Table 1).…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…We recently showed that there is no significant difference between unilateral vs bilateral TED regarding the demographics, type of thyroid disease, associated findings, and severity and activity of TED. 15 Our data indicated that patients with U-TED belonged to the same population as those with bilateral eye disease. 15 Similar to Eckstein et al, 3 we found no significant difference with regard to the age, gender, and smoking habit between Hr-TED vs Ho-TED (Table 1).…”
Section: Resultsmentioning
confidence: 51%
“…15 Our data indicated that patients with U-TED belonged to the same population as those with bilateral eye disease. 15 Similar to Eckstein et al, 3 we found no significant difference with regard to the age, gender, and smoking habit between Hr-TED vs Ho-TED (Table 1). Manji et al 28 have also stated that the presence of ophthalmopathy in both hyperthyroid and hypothyroid patients (Hashimoto thyroiditis) was not independently associated with gender.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…We have defined thyroid eye disease as presence of any one sign of thyroid eye disease (NOSPECS) while other studies have taken at least two signs [18]. In a study done in India by Mohsen Bahmani Kashkouli et al [19], the prevalence was 35.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid ophthalmopathy is usually associated with Graves’ disease; however, in 6.2% of patients with thyroid eye disease it can be associated with hypothyroidism 1. A 54-year-old woman from Tamil Nadu presented to our outpatient department with sudden onset of binocular diplopia for the past 5 months.…”
Section: Descriptionmentioning
confidence: 99%